THEATRE BY REQUEST SEBAGAI ALTERNATIF PEMBELAJARAN TEATER - M. Dinu Imansyah; G.R. Lono Lastoro Simatupang; R. M. Soedarsono (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2018)
This research discusses about "Theatre by Request" (TbR) as showcase method by Studio Theatre Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan (PPPPTK) of Seni Budaya Yogyakarta. TbR is an interactive show where audiences can choose and decide which actors will perform, the theme of the story will be staged, and to control the show depends on the performances option. This interactive performance is done by improvisation, considering the actor himself never know who will be chosen by the audience to play and what theme will be played. TbR is designed to introduce theatrical play techniques to the community, especially students. Mostly, theatre education uses drama script as a reference learning, but TbR uses theatre game as method to introduce theatre world. This research focuses on how TbR uses the game as a basis for making educative performances, especially education about the theater world itself. The results showed that theatre game is one of the alternative media to introduce theater as a performance as well as learning materials to the community, especially school children.